(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the resistance to fracture of three-element fixed partial dentof glasstment teeth restored with glass fiber posts (GFP) and cast post-and-core (CPC) retainers. Herein, 60 bovine mandibular incisors were divided into two groups (n = 30) according to the retainer type in: 1) resin composite core reinforced with GFP; and II) CPC (Cu-Al). Each pair of roots consisted of one sample, simulating a three-element fixed partial denture. The structures of the fixed three-element partial dentures were made in Ni-Cr alloy. A conventional dual resin cement (RelyX ARC - 3M Espe, USA) was used for all cementation procedures. Samples were subjected to a compressive load onto an orifice at occlusal contact region of the pontic until collapse or fracture. Normal data distribution was verified by D’Agostino & Pearson normality test. Unpaired t test was used for data analysis (α = 5%). The results showed that the the three-element fixed partial denture abutment teeth restored with composite resin cores retained by GFP presented higher fracture resistance compared to the ones restored with CPC (p=0.0009). In conclusion, the resistance to fracture of three-element fixed partial denture restored with resin composite core reinforced with glass fiber posts was higher to the one restored with post-and-core retainers.